Answer:
1/5+1/5+1/5+3/5+2/5-2/5 = 1.2
Explanation:
- First lets divide 1 and 5, how you can do this is to calculate 1(10) which equals 10, now divide it by 5 and you will get 2—all you have to do now is to just put a "0." before the 2 and you have 0.2.
- Secondly we need to add 0.2 to itself twice, "0.2 x 3 =" can be changed to 2 + 2 = x, then x + 2 = y, y = 6 in this case so lets put "0.y" as the answer to 1/5+1/5+1/5=B (B = 0.y), so now we know 1/5+1/5+1/5=0.6, lets say this is now all one variable labeled r.
- Now we have to calculate r+(3/5+2/5-2/5)=answer or we can say "a" for short. Let's use the method we used last time for 1/5 but for 3/5—We can safely say to make this easier we can calculate (3(10) = 30) ÷ 5 = t. Now 30 ÷ 5 will equal 6 because 6 x 5 = 30. so now just put "0.t" in the equation: a = r + 0.t + (2/5-2/5) = a.
- Finally we calculate 2/5 by using our easy method of 2(10) ÷ 5 = u 2(10) = 20 so 20 ÷ 5 = 4 now just put "0.u" in the equation: a = r + 0.t + 0.u = a which equals "1.2,"
a = 1.2